Analysis of amyloid and tau deposition in Alzheimer's disease using 11C-Pittsburgh compound B and 18F-THK 5351 positron emission tomography imaging - Chanisa, Chotipanich; Monchaya, Nivorn; Anchisa, Kunawudhi; Chetsadaporn, Promteangtrong; Attapon, Jantarato (World Journal of Nuclear Medicine, 2021)
This study aims to determine the deposition of 11C-Pittsburgh compound B (11C-PiB) and 18F-THK 5351 using a normal database of the optimal cut-off-points for standardized uptake value ratios (SUVRs) in Alzheimer's disease (AD) patients. Sixteen AD patients and 24 cognitively normal individuals were enrolled in this study. The optimal cutoff points for the SUVR from the normal database were used for quantitative analysis. P-mod software with the Automated Anatomical Labeling merged atlas was employed to generate automatic volumes of interest to identify different brain regions, and the SUVRs of AD patients were compared with those of the age-matched normal controls. The correlation between PiB and THK5351 deposition at matching brain regions was identified. The mean regional 11C-PiB SUVRs of the AD patients were significantly higher than the healthy controls (P < 0.05). The 11C-PiB SUVR cut-offs were 1.46–1.81, with sensitivity ranging from 81.25% to 93.75% and specificity of 100%. The mean SUVRs of 18F-THK 5351 in various regions were also significantly higher in the AD patients than in the healthy controls (P < 0.05). The inferior temporal gyrus yielded an optimum SUVR cut-off-points of 1.5 with 80% sensitivity and 83.33% specificity. The correlation of PiB and THK5351 SUVR was reported at precuneus, parietal, and occipital brain areas, with spearman's rho of 0.67, 0.66, and 0.72, respectively. Our findings allow determination of the SUVRs of 11C-PiB and 18F-THK-5351 amyloid and tau positron emission tomography tracers for clinical use, according to the normal database of the optimal cut-off-points for SUVRs in AD patients.
Keywords: 11C-Pittsburgh compound B; 18F-THK 5351; Alzheimer's disease; positron emission tomography